Heat transfer analysis of laboratory scale fast pyrolysis fluidised bed reactor - Seyed, Amirmostafa Jourabchi (AIP Publishing, 2017)
Heat transfer analysis of a fluidised bed with a bore diameter of 2.5 cm and a vertical length of 50 cm was investigated by using computational fluid dynamics (CFD) on FLUENT 15.0 educational version software. The Eulerian-Eulerian two-fluid granular model was used as the multiphase flow model to perform this simulation. A 2-D axisymmetric model was considered by using glass and stainless steel beads of 0.5 mm and 1.0 mm in diameters as the heat transfer medium to biomass. The Gidaspow model was used for the drag equation and the Gunn model was used in the interphase heat transfer coefficient determination. Heat transfer coefficient (HTC) of stainless steel beads shows to be approximately 3 times higher than that of the glass beads of the same size based on having higher thermal conductivity. At wall temperature of 500 K, stainless steel and glass beads can be fluidised by using nitrogen linear velocity of 0.7 and 0.3 m/s respectively. Under these optimum conditions, HTC reaches up to 7625 W/(m2.K) and 2900 W/(m2.K) for stainless steel and glass beads and their surface temperatures can reach up to 495 K and 480 K, respectively.